Deeper into Argumentative Bullshit - Mukerji, Nikil; Mannino, Adriano (Informal Logic)

(untitled) (Informal Logic, 2022)
In a recent paper, José Ángel Gascón extends the Frankfurtian notion of bullshit to the sphere of argumentation. On Frankfurt’s view, the hallmark of bullshit is a lack of concern for the truth of an utterance on the part of the bullshitter. Similarly, Gascón argues, the hallmark of argumentative bullshit should be viewed as a lack of concern for whether the reasons that are adduced for a claim genuinely support that claim. Gascón deserves credit for drawing attention to the idea of argumentative bullshit. Nevertheless, we argue, his treatment leaves room for further refinement as he fails to clarify important points and misidentifies several features of argumentative bullshit. In particular, Gascón’s account fails to accommodate non-Frankfurtian forms of argumentative bullshit. This paper aims to amend and extend his proposal and proposes a general account that can encompass both Frankfurtian and non-Frankfurtian forms of argumentative bullshit.